Soviet Poetic Underground in Critical and Scientific Coverage (Article Two) - N. S. Chizhov (Научный диалог)
An overview of scientific and critical works devoted to the study of Soviet uncensored poetry as a historical and literary phenomenon in general and the work of its key personalities, in particular is presented in the article. The relevance of the work is due to the lack of study of this segment of Russian literary criticism of the 20th century and the need to systematize the accumulated experience of evaluating and interpreting underground poetic culture in order to identify promising directions for its further scientific development. The article focuses, first, on the samizdat criticism of the uncensored poets of the 1980s. Such features of their artistic writing as culture-centricity, impersonality, autonomy of poetry due to the rejection of the “Aristotelian mimesis” and the reorientation of the poetic utterance to “the language itself”, etc. are characterized. Secondly, the author considers the formation in the scientific-critical discourse of the postmodernist concept of the development of Russian literature, in the light of which such underground style movements as “metarealism” and “conceptualism” are presented as the most representative phenomena of poetic postmodernism. Thirdly, it is indicated that in literary criticism of the 2000s-2010s, a number of scientific concepts were proposed that limit the research field of application of postmodern theory to Russian poetry of the second half of the 20th century (“neomodernism”, “transavant-garde”, “post-realism”). Fourth, it is determined that the development of the legacy of the Soviet poetic underground in modern literary science occurs primarily from the standpoint of a systematic study of the poetics and axiology of the work of nonconformist poets and the identification of the genetic links of their poetry with the Russian modernist and avant-garde tradition of the early 20th century.